Electrolux refrigerator brand maintains freshness and antioxidant nutrient contents of selected vegetables and fruit better than other brands - Luciana Budiati Sutanto (Indonesian Nutrition Association, 2020)
The aim of this study was to compare Electrolux refrigerator brand in maintaining freshness and antioxidant-nutrient contents of selected vegetables and fruit during the period of three weeks compare to other brands (B®, C® and D®).